Control study of improvement on grey predictive model in large time delay process - Liu Junfeng; Xia Junjian; Hu Baoan; Zhang Xinwei (2012 24th Chinese Control and Decision Conference (CCDC), 2012)
Based on ideals of improving on forecasting of the grey model, an improved grey forecasting algorithm was given. The model was built by using data accumulation with weighted method, and the model is improved by changing the initiate condition. The coefficient of the GM(1,1) model is applied to determine the prediction steps. By combining GM(1,1) model with PID, the grey predicting control system for controlling the large time delay process is proposed. The results of simulation show that, comparing with traditional PID control method, the proposed algorithm has better flexibility and robustness, and also can fairly improve the control performances.